1981
DOI: 10.1161/01.cir.64.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ejection performance in aortic stenosis.

Abstract: SUMMARY The cause of reduced ejection performance in patients with aortic stenosis is controversial. The relative contribution of afterload and contractility was evaluated in 76 patients with pure or predominant valvular aortic stenosis studied by left ventricular micromanometry and quantitative cineangiography. Thirteen patients without detectable heart disease served as controls. The ejection performance was assessed in terms of the mean normalized systolic ejection rate (MNSER, normal 2 2.0 end-diastolic vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
1
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(55 citation statements)
references
References 25 publications
0
51
1
2
Order By: Relevance
“…18 A depression in both the velocity-load and shortening-load relationship have been observed in experimental models of pressure overload. 19 By the latter relationship, shortening deficits have identified patients with either aortic stenosis or aortic insufficiency.9 20 However, the ejection fraction-afterload relationship is limited as a measure of inotropic state by the extent to which ejection fraction is dependent on resting length ("preload"). In FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 A depression in both the velocity-load and shortening-load relationship have been observed in experimental models of pressure overload. 19 By the latter relationship, shortening deficits have identified patients with either aortic stenosis or aortic insufficiency.9 20 However, the ejection fraction-afterload relationship is limited as a measure of inotropic state by the extent to which ejection fraction is dependent on resting length ("preload"). In FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that depressed ejection performance was accompanied by elevated systolic stress led Gunther and Grossman22 to conclude that afterload mismatch, and not contractile impairment, was responsible for depressed performance. However, Huber et al 20 derived subnormal values of maximum shortening velocity (Vmax) in subsets of patients with aortic stenosis in whom hypertrophy was severe. This result was corroborated by Wisenbaugh et al' with ejection fraction-afterload relationships indicating that shortening deficits could not be attributed solely to afterload mismatch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressed ejection fraction in aortic stenosis has two basic causes: afterload mismatch and contractile dysfunction. 18 Huber and colleagues 19 have demonstrated that afterload mismatch is at least partially responsible for left ventricular dysfunction in approximately three quarters of the patients who have it. The greater the role of afterload mismatch for reduced ejection fraction, the better the response to surgery.…”
Section: Patients With Severely Reduced Ejection Fraction and Aortic mentioning
confidence: 99%
“…Here there was an attempt to gain insight into the causes of hypertrophic growth cessation that occurs well before the biological limits of cardiocyte hypertrophy have been reached (3,6). This work is based on the recent experimental observation by Cooper's group (17) that during the progression of pressure overload in canine hearts the dogs broke into two groups: one group developed extensive hypertrophy while retaining normal left ventricle (LV) stress and contractile function; the LVs of the second group initially developed hypertrophy but then stopped growing and developed high LV wall stress and very depressed contractile function.…”
mentioning
confidence: 99%